3-Furan-2-yl-N-p-tolyl-acrylamide, a positive allosteric modulator of the α7 nicotinic receptor, reverses schizophrenia-like cognitive and social deficits in rats. (February 2017) - Potasiewicz, Agnieszka; Hołuj, Małgorzata; Kos, Tomasz; Popik, Piotr; Arias, Hugo R.; Nikiforuk, Agnieszka
Abstract: The cognitive impairments and negative symptoms experienced by schizophrenia patients still await effective treatment. Alpha7 nicotinic acetylcholine receptors (α7 nAChRs) have gain considerable attention in this regard. It has been recently proposed that positive allosteric modulators (PAMs) of α7 nAChRs may represent an alternative strategy to that based on orthosteric agonists. The aim of the present study is to evaluate the efficacy of PAM-2 (3-furan-2-yl- N - p -tolyl-acrylamide) against cognitive deficits and negative-like symptoms in a rat model of schizophrenia based on administration of ketamine, a NMDAR antagonist. The activity of PAM-2 was compared to that elicited by DMXBA, an α7 nAChR partial agonist. For this purpose, the attentional set-shifting task (ASST) and the novel object recognition task (NORT) were used. The efficacies of PAM-2 and DMXBA against ketamine-induced social withdrawal were assessed using the social interaction test (SIT). The results demonstrated that PAM-2 and DMXBA ameliorated ketamine-induced cognitive impairments on the ASST and NORT as well as produced pro-social activities in the SIT. Moreover, the co-administration of inactive doses of PAM-2 and antipsychotic drugs, clozapine or risperidone, reversed ketamine-induced deficits. The present findings provide further support for the concept that α7-PAMs could be used either alone or in combination with antipsychotics for schizophrenia therapy. Highlights: We evaluated the pro-cognitive and pro-social efficacies of the α7-nAChRs PAM in rats. PAM-2 reversed ketamine-induced cognitive impairments and social withdrawal. The effects of PAM-2 were comparable to those of the α7-nAChR agonist, DMXBA. Combination of PAM-2 and antipsychotics reversed impaired object recognition.